Annual variation of diffuse radiation fraction, sunshine hours, and Aerosol Optical Depth (AOD) from 1961 to 2016. - Hongfei Xie (6410837); Junfang Zhao (299684); Kaili Wang (2246485); Huiwen Peng (10739523) (2021)
Annual variation of diffuse radiation fraction, sunshine hours, and Aerosol Optical Depth (AOD) from 1961 to 2016.